Diversity, abundance, activity period, and factors affecting the appearance of wildlife around the corridors between Khao Yai- Thap Lan National Parks, Thailand by camera trapping - ronglarp - sukmasuang; Khwanrutai Charaspet; TARAPORN Panganta; MANANYA Pla-ard; NORASET KHIOESREE; JIDAPA THONGBANTHUM (Society for Indonesian Biodiversity, 2020)
Abstract. Sukmasuang R, Charaspet K, Panganta T, Pla-ard M, Khioesree N, Thongbanthum J. 2020. Diversity, abundance, activity period, and factors affecting the appearance of wildlife around the corridors between Khao Yai-Thap Lan National Parks, Thailand by camera trapping. Biodiversitas 21: xxxx. The study on diversity, abundance, activity period, and factors affecting the appearance of wildlife around the wildlife corridors was investigated using camera trap method from September 2017 to November 2018. The corridors located at the royal highway in Ban Bu Phram Subdistrict, Na Di District, Prachinburi Province, Thailand. Based on 21 camera locations, 3,172 trap nights and 6,707 captured pictures totally resulted that a total of 37 species represented by 14 orders and 26 families consisting of 13 species of herbivores, 10 species of carnivores, 10 species of aves and 4 species of reptiles were photographically recorded in the area. Among the wildlife species, 4 species were listed as endangered according to IUCN Red List including Malayan pangolin, large-spotted civet, dhole, Asian forest tortoise, 5 species were listed as vulnerable, there were Sumatran serow, gaur, sambar deer, northern pig-tailed macaque, Asian black bear, and 21 species were listed as least concerned, such as lesser oriental chevrotain, Himalayan porcupine, Asian palm civet, large Indian civet, small Indian civet, hog badger, small Asian mongoose, golden jackal, red jungle fowl, Siamese fireback, coral-billed ground cuckoo and so on. Based on photographic rate of each species, the herbivorous wildlife species represented the relative abundance index of 15.04. The carnivorous wildlife species which had the relative abundance index of 4.70, while the RAI of the aves and reptiles were 1.91 and 0.12. The activity period found that the majority were found at night. This study showed that wildlife corridors have a high influence on the appearance of wildlife, demonstrating the potential of the corridors be used by wildlife for travelling. However, the wildlife corridors should be designed to be suitable for the particular types of animals, especially by increasing the construction of underpasses for mammal at locations with the highest and the number of crossings and also must reduce noise from vehicles, especially at night.